Consequences of personalized product recommendations and price promotions in online grocery shopping. (November 2022) - Hallikainen, Heli; Luongo, Milena; Dhir, Amandeep; Laukkanen, Tommi
Abstract: Shopping convenience can be turned into a competitive advantage for online grocery retailers. Consequently, we study how personalized product recommendations (recommendation agents) and price promotions (algorithmic pricing) compensate for the negative impact that consumer's perceived cognitive effort causes on loyalty. By default, the relationship from perceived cognitive efforts to attitudinal and behavioral loyalty is negative, yet these results demonstrate that personalized price promotions lessen the negative impact, while personalized product recommendations do not have such an influence. The findings contribute to a better understanding of personalized marketing activities in today's data-driven online grocery retailing. Highlights: How effective are personalized product recommendations and price promotions in online grocery retailing? By default, perceived cognitive efforts has a negative effect on customer loyalty. Personalized price promotions rather than product recommendation lessen the negative effect in online grocery shopping. Retailers can develop ease of shopping into a competitive advantage through personalization.